Optimalisasi Media Sosial Instagram sebagai Sarana Promosi Destinasi Pariwisata Kota Bogor - Salsabila, Aliya; Pranata, Rici Tri Harpin; Cholagi, Fahmi Fuad (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Bogor City is one of the cities in Indonesia that offers a wide variety of tourist destinations. This diversity provides many options for travelers when choosing their vacation spots. However, these destinations would not be widely recognized by the public without optimal promotional efforts. This study discusses the role of the Tourism and Culture Office of Bogor City as a Regional Government Organization (OPD) under the Bogor City Government, which is responsible for developing the tourism and creative economy sectors. One of its main tasks is to promote tourism in Bogor City. Social media, particularly Instagram, is utilized as a tool for promotion. Through its official account @smilingbogorcity, the Tourism and Culture Office promotes various tourist destinations in Bogor. Using Instagram as a promotional medium provides benefits such as spreading information about tourism to a broader audience and encouraging people to visit. Effective marketing communication strategies on the @smilingbogorcity account are implemented to ensure that Bogor's tourist destinations become the top-of-mind choice for the public when planning a trip.